On ecology and design: about the Brussels school heritage and perspective on urban metabolism - Bortolotti, Andrea; Ranzato, Marco (International Planning History Society Proceedings, 2016)
The paper aims to highlight the interrelation between ecological studies and urban planning, in particular with regard to the Brussels case, given both its pioneer works and the current revival on urban metabolism. As early as the ‘70s of the last century, in continuity with the organic concept of the XIX century metropolis (the regionalism of Geddes), the ecologist Duvigneaud studied Brussels as an ecosystem. His approach integrated a scientific and socio-natural understanding of urban metabolism. Afterwards, further studies on urban metabolism have flowed into industrial ecology, the study of the material and energy circulation, narrowing the scope of investigation on urban space and nature. More recently, there has been a strong return on the debate of the Brussels urban metabolism. In order to boost the regional economic and social development as well as to meet the urban environmental challenges, new regional programs and plans are asking the urban projects to integrate a strong metabolic perspective. However, it remains to better understand how and to which extent the discipline of urbanism can actually draw from urban metabolism studies, and, in turn, what it can bring to the research field. In answering this question, we look back in particular to the influences and relations between ecological studies and urban design and planning in the recent history of Brussels. On the one hand, the results show that, despite the rising interest in the subject, until now, design and planning practice, in Belgium, seems to have little learnt from urban metabolism studies, showing few significant contributions to the discipline. On the other hand, it clearly emerges that stronger socio-natural perspective is needed in order for urban design and planning to steer the transformation of the city towards a more resilient urban metabolism.